Cardiometabolic risk is unraveled by color Doppler ultrasound of the clitoral and uterine arteries in women consulting for sexual symptoms - I. Scavello (Nature Portfolio, 2021)
Abstract Female sexual dysfunction (FSD) may be a mirror of a poor cardiometabolic state. In a small pilot study enrolling 71 women with FSD, we previously demonstrated that clitoral Pulsatility Index (PI) evaluated by using color Doppler ultrasound (CDU), reflecting vascular resistance, was associated with cardiometabolic risk factors. Data on uterine CDU in this context are lacking. First, to confirm previously reported data on the direct association between clitoral PI and cardiometabolic risk factors on a larger study population of women consulting for sexual symptoms; second, to investigate eventual similar correlations between cardiometabolic risk factors and CDU parameters of the uterine artery. We also ascertained whether uterine artery PI, similarly to what had previously been observed for clitoral artery PI, was directly related to body image uneasiness and psychopathological symptoms, assessed by validated questionnaires. N = 230 women consulting our clinic for sexual symptoms were examined with clitoral CDU and blood sampling and were asked to fill out the Female Sexual Function Index, the Middlesex Hospital Questionnaire (MHQ) and the Body Uneasiness Test (BUT). In a subgroup of women (n = 164), we also performed transvaginal CDU with measurement of uterine artery parameters. At multivariate analysis, we found a direct association between clitoral PI and body mass index (BMI) (p = 0.004), waist circumference (WC) (p = 0.004), triglycerides (p = 0.006), insulin (p = 0.029) and HOMA-IR (p = 0.009). Furthermore, a correlation between obesity and Metabolic Syndrome (MetS) and a higher clitoral PI was observed (p = 0.003 and p = 0.012, respectively). Clitoral PI was also correlated with MHQ-S (p = 0.010), a scale exploring somatized anxiety symptoms, and BUT-B Positive Symptom Distress Index (p = 0.010), a measure of body image concerns. Similarly, when investigating the uterine artery, we were able to demonstrate an association between its PI and BMI (p < 0.0001), WC (p = 0.001), insulin (p = 0.006), glycated haemoglobin (p =  < 0.0001), and HOMA-IR (p = 0.009). Women diagnosed with obesity and MetS showed significantly higher uterine PI values vs. those without obesity or MetS (p = 0.001 and p = 0.004, respectively). Finally, uterine PI was associated with BUT-A Global Severity Index (p < 0.0001) and with several other BUT-A subdomains. Vascular resistance of clitoral and uterine arteries is associated with cardiometabolic risk factors and body image concerns in women consulting for sexual symptoms. If further confirmed in different populations, our data could suggest CDU, a common examination method, as a useful tool for an identification—and possible correction—of cardiometabolic risk factors.